1992
DOI: 10.1177/107110079201300901
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Muscle Imbalance in the Leg in Symptomatic Forefoot Pes Cavus: A Multidisciplinary Study

Abstract: The cross-sectional areas of the peroneal and anterior muscle compartments at the same level in the upper leg were measured using magnetic resonance imaging in 41 cases of forefoot pes cavus. The pes cavus group included idiopathic cases and pes cavus associated with Charcot-Marie-Tooth disease, Friedreich's ataxia, cerebral palsy, status postpoliomyelitis, nerve trauma, and spinal cord tethering. Thirty-nine of these cases were symptomatic. The results were compared with studies of 11 normal controls. It was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(36 citation statements)
references
References 30 publications
0
36
0
Order By: Relevance
“…Chronic neuropathies developing before cessation of the growth period frequently give rise to foot deformity [1,42]. Forefoot pes cavus probably reflects muscle weakness and imbalance involving intrinsic foot musculature, lower leg musculature or both [44]. Presence of pes cavus is often taken as evidence of an inherited neuropathy such as CMT disease [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic neuropathies developing before cessation of the growth period frequently give rise to foot deformity [1,42]. Forefoot pes cavus probably reflects muscle weakness and imbalance involving intrinsic foot musculature, lower leg musculature or both [44]. Presence of pes cavus is often taken as evidence of an inherited neuropathy such as CMT disease [25].…”
Section: Discussionmentioning
confidence: 99%
“…Forefoot pes cavus deformity is a cardinal manifestation of CMT [26,44]. Chronic neuropathies developing before cessation of the growth period frequently give rise to foot deformity [1,42].…”
Section: Discussionmentioning
confidence: 99%
“…This deformity is often associated with scoliosis and it may be secondary to altered balance or to disorders of the central nervous system, as shown by Carpintero et al (1994). In a multidisciplinary study of Tynan et al (1992), it was found that in the majority of cases of claw foot, the peroneal compartment was enlarged in relation to the anterior compartment when compared to the normal controls. Recent studies have shown that claw foot is one of the risk factors, including also flat foot, restricted ankle dorsiflexion, increased hind foot inversion, to predispose people toward lower extremity overuse injuries, as indicated by the studies of Kaufman et al (1999) and Keegan et al (2002).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with CharcotMarie-Tooth disease, an inherited neurological disorder primarily affecting the peripheral nerves in the lower extremities, frequently exhibit pes cavus resulting from weakness in the peroneus brevis and tibialis anterior muscles relative to their natural antagonist tibialis posterior and peroneus longus muscles, respectively [17,18]. Similar imbalances in the peroneal and anterior compartments of the leg muscles have been shown to contribute to cases of pes cavus associated with other pathologies [16]. Additionally, young adults with pes planus demonstrated different sizes and thicknesses of the intrinsic and extrinsic muscles of the foot on ultrasound compared with normal controls [42].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with posterior tibial tendon dysfunction, a common acquired flatfoot deformity, have lower ankle and hip muscle strength compared to non-patients [14], and the degree of deformity is inversely related to leg muscle strength [15]. Imbalance of the muscles that control the foot, but originate in the lower leg has been implicated in the etiology of both idiopathic and disease-related pes cavus (high arches) [16][17][18]. Further, evidence from studies of runners suggests that weakness in lower leg [19] and hip-stabilizing muscles [20] can lead to disturbed lower extremity mechanics, resulting in over-pronation of the foot.…”
Section: Introductionmentioning
confidence: 99%